Erodibility of two texturally different aggregates as affected by their size and moisture contents under different land uses in semi-arid tropical environments - HADDA, M.S.; SINGH, BALBIR (Journal of Soil and Water Conservation, 2024)
The erodibility of different sized aggregates could vary with change in moisture content, land use and soil texture. Therefore, an attempt was made to evaluate the erodibility of aggregate under four land uses, four aggregate sizes and three antecedent soil moisture contents encompassing two different soils textural classes in conducted investigation following completely randomized block design using a simulated single raindrop technique. The natural aggregates were collected from two texturally different soils that is, sandy loam and loamy sand at D R Bhumbla Zonal Research Station for Kandi Area, Ballowal– Saunkhri, district SBS Nagar, Punjab. These aggregates were exposed to simulated single raindrops of sizes 2.5 and 4.5 mm, respectively. The EISRT (Single raindrop technique –based erodibility index) was least under grasses followed by forests, arable and fallow in both types of soils. The erodibility of aggregates were higher in magnitude from smaller sized to bigger sized and from air dry to saturation moisture content , irrespective of land use in both types of soils. However, the erodibility of aggregates was higher in magnitude when aggregates were air- dried than that over other moisture contents with 4.5 mm raindrop size. Whereas, the loamy sand sized aggregates were more erodible compared to sandy loam aggregates under different land uses.